PENGARUH LINGKUNGAN KERJA, BEBAN KERJA, DAN KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN PADA NUSA DUA BEACH HOTEL & SPA - Kadek Sri Damayanthi; I Ketut Setia Sapta; I Nengah Sudja (EMAS, 2021)
Turnover Intention of Nusa Dua Beach Hotel & Spa employees is still classified as not good because the Turnover Intention rate ranges from 9.6% - 13.74%. This high turnover intention will certainly have an impact on the activities and operations of Nusa Dua Beach Hotel & Spa. This study aims to determine empirically the effect of work environment, workload, and compensation on employee turnover intention at Nusa Dua Beach Hotel & Spa. The population used in this study were all employees of the Nusa Dua Beach Hotel & Spa, totaling 329 people. In this study, the authors narrowed the population using the Slovin technique in order to obtain 77 respondents. The sampling technique used is proportional random sampling, which is sampling that takes into account the considerations of elements or categories in the study population. The analysis technique used in this research is multiple linear regression analysis techniques. Before the analysis is carried out, the test is first carried out and continued with the classical assumption test consisting of the normality test, multicollinearity test, and heteroscedasticity test. The results showed that the work environment has a negative effect on turnover intention, workload has a positive effect on turnover intention, and compensation has a negative effect on turnover intention at Nusa Dua Beach Hotel & Spa.